Monetary Policy Transmission in Emerging Asia : The Role of Banks and the Effects of Financial Globalization - Ananchotikul, Nasha (IMF Working Papers; Working Paper ;, 2015)
Given the heavy reliance on bank lending as the main source of financing in most Asian economies, banks could potentially play a pivotal role in monetary policy transmission. However, we find that Asia's bank lending channel or, more broadly, credit channel of domestic monetary policy is not very strong at the aggregate level. Using bank-level data for nine Asian economies during 2000-2013, we show that heterogeneity of bank characteristics (e.g., ownership type, financial position), degree of foreign bank penetration of the domestic banking sector, and global financial conditions all have a bearing on the response of domestic credit to changes in domestic monetary policy, and may account for the apparently weak credit channel at aggregate level.